Influence of Green Accounting and Environmental Performance on Financial Performance Through CSR - Amin Wijoyo; Nastasya Cindy (Dinasti Publisher, 2025)
The purpose of this study is to obtain empirical evidence regarding the effect of green accounting and environmental performance on corporate social responsibility, on financial performance, and on financial performance through corporate social responsibility as a mediating variable. Primary data was used in the study in which the number of samples in this study was 33 companies engaged in the energy and chemical sectors and listed on the IDX during 2021-2023. This research variable consists of three types of variables, namely independent variables consisting of green accounting and environmental performance; the mediating variable is corporate social responsibility; and the dependent variable is financial performance. Partial test findings state that the dependent variable is not significantly influenced by green accounting with or without mediating variables, while with or without mediating variables it can be significantly influenced by environmental performance. Simultaneously, the independent variables have a significant effect on the dependent variable both with and without the mediating variable.